Applying Transactional NPS for Customer Journey Insight: Case Experiences and Lessons Learned. Issue 3 (3rd July 2018) - Følstad, Asbjørn; Kvale, Knut
ABSTRACT: While the concept of "customer journeys" is widely taken up to support service design and management, practical frameworks for routine monitoring of customer experience in the context of customer journeys are lacking. This article proposes a framework for applying the widely used transactional Net Promoter Score (NPS) as a means for gathering insight into customers' experiences of a customer journey. We present lessons learnt from three case trials of the framework elements within a telecom service provider, involving the analysis of more than 1, 700 quantitative and qualitative customer responses from transactional NPS surveys.